2019
DOI: 10.3390/w11030466
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effects of Land Use on Hydrochemistry and Soil Microbial Diversity

Abstract: The objectives of this study were to compare the influence of land use, to determine which land has an impact on hydrochemistry and to clarify the impact of land use on soil microbial diversity and the correlation between hydrochemistry and soil microbial diversity. The impacts were assessed through chemical and biological data from 4 land-use groups. The results showed that soil microbial diversity and water chemical composition were different under different land uses. There was a strong correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Most of the microorganisms were found to have high positive correlation to different soil quality parameters except for pH and Pb. Among the microorganisms, Gemmatimonadetes was found to have positive correlation with r value of 0.899 to pH while negative correlation (r value: −0.686 to −0.931) to other parameters Proteobacteria survives through symbiosis with bacteria and other plant roots, and the high proportion of Proteobacteria have significant effect on nitrogen reduction and plant growth in the facility [47][48][49][50]. Actinobacteria is a microorganism that parasites on plant roots to create root holes, perform nitrogen fixation and reduce heavy metals [51,52].…”
Section: Microbial Distribution Along the Plant Zone Of The Hssf Cwmentioning
confidence: 96%
“…Most of the microorganisms were found to have high positive correlation to different soil quality parameters except for pH and Pb. Among the microorganisms, Gemmatimonadetes was found to have positive correlation with r value of 0.899 to pH while negative correlation (r value: −0.686 to −0.931) to other parameters Proteobacteria survives through symbiosis with bacteria and other plant roots, and the high proportion of Proteobacteria have significant effect on nitrogen reduction and plant growth in the facility [47][48][49][50]. Actinobacteria is a microorganism that parasites on plant roots to create root holes, perform nitrogen fixation and reduce heavy metals [51,52].…”
Section: Microbial Distribution Along the Plant Zone Of The Hssf Cwmentioning
confidence: 96%
“…The soil CO 2 content was the highest in L02. At the same depth, the soil CO 2 concentrations with different land uses were different [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The soil CO 2 concentration is higher than atmospheric CO 2 (Zhang et al 2019), and with an annual global efflux from soil respiration equivalent to approximately 10% of atmospheric CO 2 (Liu and Huang 2015). Soil is the second largest carbon pool after the ocean and the main source of atmospheric CO 2 (Jenkinson et al 1991;Robert 2004); approximately 77 × 10 15 gCyr −1 a −1 CO 2 is released into the atmosphere through soil respiration (Raich and Potter 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Field experiments in 2016 showed that different land use patterns had different effects on soil CO 2 concentration and microbial community composition. A previous report of these data was discussed by Zhang (Zhang et al 2019). Based on field observation data, laboratory experiments were conducted to analyze the correlation between the soil CO 2 and water chemical composition under natural conditions.…”
Section: Introductionmentioning
confidence: 99%